High-strength aluminum material and preparation process thereof
By introducing multi-stage reinforced structure and three-dimensional network structure design into the aluminum matrix, the limitations of traditional aluminum alloys in terms of strength, hardness and high temperature stability are solved, and the excellent performance of high-strength aluminum materials in extreme environments is achieved.
Patent Information
- Application Number
- CN202411738966.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional aluminum alloys have limitations in strength, hardness and high temperature stability, and are difficult to meet the requirements of use in extreme environments.
A high-strength aluminum material is used, and its composition includes aluminum, copper, magnesium, manganese, aluminum carbonitride, silicon carbide, carbon nanotubes and zinc. It is formed by superlattice structure design, introduction of nanotwin boundaries, gradient distribution, nanoprecipitation and multi-scale enhancement and other technical means.
It significantly improves the mechanical properties, corrosion resistance, wear resistance and high temperature stability of the material, and can perform well in complex stress environments.
Smart Images

Figure CN119592887A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum materials, and in particular to a high-strength aluminum material and a preparation process thereof. Background Art
[0002] With the rapid development of modern industry, the requirements for material performance are increasing day by day. Especially in the fields of aerospace, transportation, electronic packaging, etc., there is an urgent need for high-strength, lightweight and well-processed metal materials. Aluminum and its alloys are widely used due to their low density, good electrical and thermal conductivity and easy processing. However, traditional aluminum alloys still have limitations in strength, hardness and high-temperature stability, and it is difficult to meet the requirements of use in extreme environments.
[0003] Therefore, we proposed a high-strength aluminum material and its preparation process to solve the above problems. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high-strength aluminum material and a preparation process thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A high-strength aluminum material comprises the following components in parts by weight: 80-85 parts of aluminum, 2-4 parts of copper, 1-3 parts of magnesium, 0.5-1.5 parts of manganese, 1-3 parts of aluminum carbonitride, 1-3 parts of silicon carbide, 0.1-0.5 parts of carbon nanotubes, and 1-2 parts of zinc.
[0007] As the preferred technical solution:
[0008] The high-strength aluminum material as described above includes the following components in parts by weight: 83 parts of aluminum, 3 parts of copper, 2 parts of magnesium, 0.8 parts of manganese, 2 parts of aluminum carbonitride, 2 parts of silicon carbide, 0.4 parts of carbon nanotubes, and 1 part of zinc.
[0009] As described above, the particle size of the aluminum presents a trimodal distribution, wherein the peak value of the coarse particles is at 80±5μm, the peak value of the fine particles is at 0.7±0.1μm, and the intermediate peak is at 10±1μm; the aluminum is a matrix, and the atoms therein form an ordered nanostructure through self-assembly; the copper is a reinforcing phase, and copper presents a gradient distribution in the aluminum matrix; the magnesium exists in the aluminum matrix in the form of a nano-precipitated phase; the manganese reinforces the aluminum matrix at multiple scales, including nanometers and micrometers; the silicon carbide forms a three-dimensional network structure in the aluminum matrix, providing a full range of reinforcement effects.
[0010] A high-strength aluminum material as described above, wherein aluminum is used as a matrix, a superlattice structure design is adopted, and / or nano-twin boundaries are introduced into the aluminum matrix; the copper adopts a core-shell structure, the core is pure copper, the shell is copper oxide, and the copper and the aluminum matrix form a layered composite structure; the magnesium is embedded in the aluminum matrix in a nano-columnar structure, and a coherent interface is formed between the magnesium and the aluminum matrix; the manganese is dispersed in the aluminum matrix in the form of nanoclusters; the aluminum carbonitride is embedded in the aluminum matrix in a nano-sheet structure; the silicon carbide is dispersed in the aluminum matrix in a nano-wire structure; and the carbon nanotubes form a nano-bridge structure in the aluminum matrix.
[0011] A second aspect of the present invention provides a process for preparing a high-strength aluminum material, comprising the following steps:
[0012] S1: Aluminum powder is subjected to a particle size screening process to obtain aluminum particles with a trimodal distribution. The aluminum matrix is designed with a superlattice structure. Nano twin boundaries are introduced into the aluminum matrix by keeping it at 500°C for 2 hours and then rapidly cooling it to room temperature to increase the strength and hardness of the material.
[0013] S2: Partially oxidize the pure copper powder, heat it to 300°C in an inert gas environment with an oxygen content of 5% and keep it warm for 1 hour to form a copper powder with a core-shell structure. Subsequently, mix the copper powder with the aluminum matrix treated in step S1 to ensure uniform distribution;
[0014] S3: On the mixed aluminum matrix, magnesium is deposited by physical vapor deposition technology to form a nano-columnar structure and embedded in the aluminum matrix. At the same time, manganese is dispersed in the aluminum matrix in the form of nano-clusters by chemical vapor deposition. These clusters can serve as a strengthening phase to improve the hardness and wear resistance of the material.
[0015] S4: Aluminum carbonitride nanosheets are uniformly embedded into the aluminum matrix by high-energy ball milling, silicon carbide nanowires are uniformly dispersed in the aluminum matrix by ultrasonic dispersion to form a three-dimensional network structure, and carbon nanotubes are introduced into the aluminum matrix to form a nano-bridge structure to connect different aluminum grains;
[0016] S5: the composite material prepared in S4 is pressed and molded, and the pressure is maintained at 450°C and 50 MPa for 30 minutes, and the molded material is subjected to aging treatment at 700°C for 4 hours;
[0017] S6: Cutting, grinding and machining the heat-treated aluminum material to obtain high-strength aluminum material.
[0018] As the preferred technical solution:
[0019] In the above-mentioned process for preparing a high-strength aluminum material, S1 specifically comprises:
[0020] S11: Aluminum powder is selected as raw material, and is screened by a particle size screening device. A multi-stage screen design is adopted to classify the aluminum powder into three particle size ranges: coarse particles, fine particles, and intermediate particles. The three particles are collected separately for subsequent use;
[0021] S12: Using superlattice structure design method, the microstructure of aluminum matrix is designed, and the lattice parameters and atomic arrangement are optimized through computer simulation technology;
[0022] S13: mixing the screened aluminum particles, and then placing them in a high-temperature furnace for heat treatment at a temperature of 500° C. for a holding time of 2 hours. During this process, the atoms between the aluminum particles diffuse and rearrange to gradually form an aluminum matrix with a superlattice structure. At the same time, by controlling the oxygen content in the heat treatment atmosphere, a dense oxide film is ensured to be formed on the surface of the aluminum matrix.
[0023] S14: After the heat treatment is completed, the aluminum substrate is rapidly cooled from a high temperature state to room temperature;
[0024] S15: Use high-precision transmission electron microscope equipment to observe the microstructure of the aluminum matrix, confirm the existence and distribution of nano twin boundaries, and verify whether the strength and hardness of the material meet the expected goals through hardness testing and tensile test mechanical properties testing methods;
[0025] S16: The verified aluminum substrate is post-processed, including surface cleaning and drying. After the processing is completed, the aluminum substrate is stored in a dry, oxygen-free environment for subsequent use.
[0026] In the above-mentioned process for preparing a high-strength aluminum material, S2 specifically comprises:
[0027] S21: placing the copper powder in a vacuum drying oven and drying it at 100° C. for 2 hours, and then constructing an inert gas environment with an oxygen content of 5% to ensure the stability and uniformity of the oxidation process;
[0028] S22: spreading the pretreated pure copper powder evenly in a ceramic boat, placing the ceramic boat in a tube furnace, slowly heating to 300° C., controlling the heating rate at 5° C. / min, and keeping the temperature at 300° C. for 1 hour to form a thin copper oxide shell layer, while the internal copper core remains in a metallic state, thereby forming a core-shell structure;
[0029] S23: After the oxidation treatment is completed, turn off the heating source, let the tube furnace cool naturally to room temperature, and control the cooling rate within 10°C / min. After complete cooling, gently scrape the core-shell structure copper powder from the ceramic boat;
[0030] S24: taking the aluminum substrate treated in step S1, cleaning the surface, and then placing the aluminum substrate in a vacuum drying oven and drying it at 80° C. for 1 hour;
[0031] S25: using a high-speed mechanical stirrer or a ball mill to mix the core-shell structure copper powder and the aluminum matrix uniformly, and the mixing time is controlled within 30-60 minutes until the copper powder is uniformly dispersed in the aluminum matrix without obvious agglomeration;
[0032] S26: After the mixing is completed, the mixture is placed in a vacuum drying oven and dried at 120° C. for 2 hours. After drying, the mixture is lightly compacted.
[0033] In the above-mentioned process for preparing a high-strength aluminum material, S3 specifically comprises:
[0034] S31: performing surface purification treatment on the aluminum substrate mixed evenly in step S2, placing the treated aluminum substrate in a vacuum chamber of a PVD device, preparing a magnesium target, and installing it on the target position of the PVD device;
[0035] S32: starting the PVD equipment to sputter the magnesium target material, so that magnesium atoms form a continuous and uniform nano-columnar structure on the surface of the aluminum substrate;
[0036] S33: After completing the physical vapor deposition of magnesium, the operation of chemical vapor deposition of manganese nanoclusters is performed directly in the same vacuum chamber without moving the aluminum substrate. First, a precursor gas containing manganese elements is introduced to allow manganese atoms to self-assemble on the surface of the aluminum substrate to form nanoclusters. During the deposition process, an inert gas is introduced for dilution. After the deposition is completed, it is naturally cooled to room temperature, and then the aluminum substrate is slightly surface treated.
[0037] In the above-mentioned process for preparing a high-strength aluminum material, S4 specifically comprises:
[0038] S41: mixing the aluminum matrix treated in step S3 with aluminum carbonitride nanosheets, placing the mixture in a ball milling tank of a high-energy ball mill, and uniformly embedding the aluminum carbonitride nanosheets into the aluminum matrix through the mechanical force of the high-energy ball milling;
[0039] S42: adding silicon carbide nanowires to a mixture containing an aluminum matrix and embedded aluminum carbonitride nanosheets, and then ultrasonically treating the mixture using an ultrasonic disperser, so that the silicon carbide nanowires are uniformly dispersed in the aluminum matrix through ultrasonic dispersion to form a three-dimensional network structure;
[0040] S43: adding carbon nanotubes to the above mixture, using a solution mixing method, first dispersing the carbon nanotubes in a solvent, then adding the aluminum matrix mixture, and making the carbon nanotubes evenly adhere to the surface of the aluminum particles through mechanical stirring and ultrasonic treatment, and then removing the solvent through vacuum drying to obtain an aluminum matrix mixture containing carbon nanotubes.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] Complementarity between aluminum matrix and reinforcement phase: Aluminum, as a lightweight matrix, provides good processability and corrosion resistance. The addition of metal reinforcement phases such as copper, magnesium, and manganese forms a multi-level reinforcement structure in the aluminum matrix through gradient distribution, nano-precipitation, etc., which significantly improves the mechanical properties of the material.
[0043] Multi-dimensional strengthening of non-metallic reinforcement phases: Non-metallic reinforcement phases such as aluminum carbonitride, silicon carbide, and carbon nanotubes construct a three-dimensional network structure in the aluminum matrix, enhancing the strength, hardness, and wear resistance of aluminum materials at multiple scales. This multi-dimensional synergy enables aluminum materials to perform well in complex stress environments.
[0044] Strengthening effect of superlattice structure and nano-twin boundaries: Through superlattice structure design and introduction of nano-twin boundaries, the lattice structure of the aluminum matrix is optimized and the bonding force between atoms is enhanced, thereby improving the overall strength and deformation resistance of the material.
[0045] Uniformity of nanoscale dispersion: The uniform dispersion of each component at the nanoscale ensures good interface bonding between the reinforcement phase and the aluminum matrix, reduces the possibility of stress concentration and interface failure, and further improves the overall performance of the material.
[0046] In summary, the present invention achieves significant improvements in mechanical properties, corrosion resistance, wear resistance, etc. through multi-component synergistic enhancement, synergistic optimization of structure and performance, and synergistic improvement of process and performance, providing high-performance material solutions for a wide range of application fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is the SEM morphology of the tensile fracture of the product of Example 3 of the present invention;
[0048] Figure 2 It is a data line chart of the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. When there is a conflict, the definitions in this specification shall prevail. "When mass, concentration, temperature, time, or other values or parameters are expressed as ranges, preferred ranges, or a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately.
[0050] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0051] A high-strength aluminum material comprises the following components in parts by weight: 80-85 parts of aluminum, 2-4 parts of copper, 1-3 parts of magnesium, 0.5-1.5 parts of manganese, 1-3 parts of aluminum carbonitride, 1-3 parts of silicon carbide, 0.1-0.5 parts of carbon nanotubes, and 1-2 parts of zinc.
[0052] Specifically, the particle size of aluminum presents a trimodal distribution, with the coarse particle peak at 80±5μm, the fine particle peak at 0.7±0.1μm, and the intermediate peak at 10±1μm; aluminum is the matrix, and the atoms in it form an ordered nanostructure through self-assembly; copper is the reinforcing phase, and copper presents a gradient distribution in the aluminum matrix; magnesium exists in the aluminum matrix in the form of a nano-precipitated phase; manganese reinforces the aluminum matrix at multiple scales, including nanometers and micrometers; silicon carbide forms a three-dimensional network structure in the aluminum matrix, providing a full range of reinforcement effects.
[0053] In high-strength aluminum materials, to achieve the above characteristics, we can refer to the following embodiments for specific operations:
[0054] 1. Trimodal distribution of aluminum particles
[0055] Peak value of coarse particles: By screening or controlling the preparation process of aluminum powder, ensure that the peak value of coarse particles is in the range of 75-85μm, with 80μm as the center. Such particles can provide good filling effect and mechanical support.
[0056] Fine particle peak: Nano-grinding or other nano-preparation techniques are used to make the peak of fine particles in the range of 0.6-0.8μm, centered at 0.7μm. These fine particles help increase the specific surface area of the material and improve the interface bonding ability with other components.
[0057] Intermediate peak: Through precise particle grading technology, the particles of the intermediate peak are controlled within the range of 9-11μm, with 10μm as the center. These particles play a bridging role in the material, helping to enhance the overall structural stability of the material.
[0058] 2. Self-assembled nanostructures on aluminum substrates
[0059] Atomic self-assembly: During the preparation of the aluminum matrix, the aluminum atoms are self-assembled into orderly nanostructures by controlling the temperature, pressure and cooling rate. These nanostructures can significantly improve the mechanical properties and corrosion resistance of the material.
[0060] 3. Gradient distribution of copper
[0061] Copper content control: The copper element is gradually introduced into the aluminum matrix, and the copper content and distribution are controlled to make it present a gradient change in the aluminum matrix. For example, the copper content can gradually increase or decrease from one side of the aluminum matrix to the other side to form a continuous gradient distribution.
[0062] 4. Nano-precipitation phase of magnesium
[0063] Nano-precipitation: Add an appropriate amount of magnesium to the aluminum matrix, and use heat treatment and other process methods to make the magnesium evenly dispersed in the aluminum matrix in the form of nano-precipitates. These nano-precipitates can effectively improve the strength and hardness of the material.
[0064] 5. Multi-scale enhancement of manganese
[0065] Multi-scale addition: Both nano-scale and micro-scale manganese particles are introduced into the aluminum matrix. Nano-scale manganese particles can provide better interface bonding and strengthening effects, while micro-scale manganese particles help to enhance the overall structural stability of the material.
[0066] 6. Three-dimensional network structure of silicon carbide
[0067] Three-dimensional network construction: SiC particles are introduced into the aluminum matrix by pressureless self-infiltration or other suitable processes, and controlled to form a continuous three-dimensional network structure. This structure can provide a full range of reinforcement effects and significantly improve the mechanical properties and thermal stability of the material.
[0068] Specific data
[0069] The particle size distribution of aluminum particles: coarse particles 75-85μm (peak 80μm), fine particles 0.6-0.8μm (peak 0.7μm), intermediate peak 9-11μm (peak 10μm).
[0070] Copper gradient distribution: For example, the copper content gradually increases from 5% to 15% from one side of the aluminum matrix to the other side.
[0071] Magnesium nano-precipitation phase: The precipitate phase size is in the range of 10-100nm and is evenly distributed in the aluminum matrix.
[0072] Manganese particle size: The nano-scale manganese particle size is in the range of 1-100nm, and the micro-scale manganese particle size is in the range of 1-10μm.
[0073] Silicon carbide three-dimensional network structure: The silicon carbide particle size is in the range of 0.1-10μm, forming a continuous three-dimensional network structure, occupying 10-30% of the volume of the aluminum matrix.
[0074] It should be noted that aluminum is used as the matrix, a superlattice structure design is adopted, and / or nano twin boundaries are introduced into the aluminum matrix. These interfaces can effectively hinder dislocation movement, thereby improving the strength and hardness of the material; copper adopts a core-shell structure, with the core being pure copper and the shell being copper oxide, to enhance the interfacial bonding with the aluminum matrix and improve corrosion resistance. Copper and the aluminum matrix form a layered composite structure, and by alternately stacking different material layers, a synergistic improvement in strength and toughness is achieved; magnesium is embedded in the aluminum matrix in a nano-columnar structure, which can provide additional strengthening effects while maintaining good Ductility: a coherent interface is formed between magnesium and the aluminum matrix, which reduces the interfacial energy and improves the stability and strength of the material. Manganese is dispersed in the aluminum matrix in the form of nanoclusters, which can act as a reinforcing phase to improve the hardness and wear resistance of the material. Aluminum carbonitride is embedded in the aluminum matrix in a nanosheet structure to increase the hardness and scratch resistance of the material. Silicon carbide is dispersed in the aluminum matrix in a nanowire structure, which can provide excellent mechanical properties and thermal stability. Carbon nanotubes form a nanobridge structure in the aluminum matrix, connecting different aluminum grains and improving the conductivity and mechanical properties of the material.
[0075] In the design and preparation process of high-strength aluminum materials, in order to obtain the above characteristics, we can refer to the following embodiments for specific operations:
[0076] Example
[0077] 1. Superlattice structure design and introduction of nano-twin boundaries
[0078] High-purity aluminum is selected as the base material, and the optimal grain size is determined through molecular dynamics simulation to achieve the formation of stacking faults and twins. Experiments show that stacking faults / twins can be formed when the aluminum grain size is less than 35nm. Through cryo-milling or other nano-processing techniques, we can ball-mill aluminum powder to the nanoscale to form nano-twin boundaries in the aluminum matrix. These interfaces can effectively hinder dislocation movement, and this structure can increase the maximum strength of the material by about 8 times.
[0079] 2. Core-shell structure design of copper
[0080] Using chemical vapor deposition or other suitable methods, a copper oxide shell is formed on the outside of the pure copper particles to create a core-shell structure. The core is pure copper and the shell is copper oxide. This structure not only enhances the interfacial bonding with the aluminum matrix, but also improves corrosion resistance. These core-shell copper particles are alternately stacked with the aluminum matrix to form a layered composite structure to achieve a synergistic improvement in strength and toughness.
[0081] 3. Magnesium nanocolumnar structure embedding
[0082] Nanocolumnar magnesium structures are embedded in the aluminum matrix through techniques such as nanoimprinting or electrochemical deposition. This structure can provide additional strengthening while maintaining good ductility. Studies have shown that the coherent interface formed between magnesium and the aluminum matrix can reduce the interfacial energy, thereby improving the stability and strength of the material.
[0083] 4. Manganese nanocluster dispersion
[0084] Manganese nanoclusters are dispersed in the aluminum matrix using techniques such as chemical reduction or physical vapor deposition. These clusters act as a reinforcement phase and can significantly improve the hardness and wear resistance of the material.
[0085] 5. Introduction of aluminum carbonitride, silicon carbide and carbon nanotubes
[0086] Nano-sheet aluminum carbonitride, nano-wire silicon carbide, and carbon nanotubes forming nano-bridge structures are embedded in the aluminum matrix through chemical vapor deposition or physical mixing. These structures increase the hardness, scratch resistance, mechanical properties, and thermal stability of the material, and improve the conductivity of the material.
[0087] Specific data
[0088] Aluminum grain size: less than 35nm to enable stacking fault / twin formation.
[0089] The core-shell structure of copper: the diameter of the inner core of pure copper is about 50-100nm, and the thickness of the oxide outer shell is about 5-10nm.
[0090] Nano-columnar structure of magnesium: the diameter is about 10-50nm, and the height can be adjusted as needed.
[0091] Manganese nanoclusters: The diameter is about 2-10nm, evenly dispersed in the aluminum matrix.
[0092] Embodiment 1
[0093] A high-strength aluminum material comprises the following components in parts by weight: 80 parts of aluminum (Chinalco), 2 parts of copper (Northeast Light Alloy Co., Ltd.), 1 part of magnesium (Northeast Light Alloy Co., Ltd.), 0.5 parts of manganese (Northeast Light Alloy Co., Ltd.), 1 part of aluminum carbonitride (Chinalco), 1 part of silicon carbide (Chinalco), 0.1 part of carbon nanotube (Chinalco), and 1 part of zinc (Northeast Light Alloy Co., Ltd.).
[0094] A preparation process of a high-strength aluminum material proposed in the embodiment comprises the following steps:
[0095] S1: Aluminum powder is subjected to a particle size screening process to obtain aluminum particles with a trimodal distribution, namely coarse particles, fine particles and intermediate particles. The aluminum matrix is designed with a superlattice structure. Nano twin boundaries are introduced into the aluminum matrix by keeping it at 500°C for 2 hours and then rapidly cooling it to room temperature to increase the strength and hardness of the material.
[0096] S2: Partially oxidize the pure copper powder, heat it to 300°C in an inert gas environment with an oxygen content of 5% and keep it warm for 1 hour to form a copper powder with a core-shell structure. Subsequently, mix the copper powder with the aluminum matrix treated in step S1 to ensure uniform distribution;
[0097] S3: Physical vapor deposition is used to deposit magnesium on the mixed aluminum matrix to form a nano-columnar structure and embed it into the aluminum matrix. At the same time, chemical vapor deposition is used to disperse manganese in the aluminum matrix in the form of nano-clusters. The cluster size is controlled at 5nm. These clusters can serve as a strengthening phase to improve the hardness and wear resistance of the material.
[0098] S4: Aluminum carbonitride nanosheets are uniformly embedded into the aluminum matrix through high-energy ball milling. The thickness of the nanosheets is controlled at 10nm to increase the hardness and scratch resistance of the material. Silicon carbide nanowires are uniformly dispersed in the aluminum matrix through ultrasonic dispersion to form a three-dimensional network structure, providing a full range of reinforcement effects. Carbon nanotubes are introduced into the aluminum matrix to form a nano-bridge structure to connect different aluminum grains and improve the conductivity and mechanical properties of the material.
[0099] S5: The composite material prepared in S4 is pressed and formed, and the pressure is maintained at 450°C and 50MPa for 30 minutes. The formed material is subjected to aging treatment at 700°C for 4 hours to eliminate internal stress, optimize microstructure, and further improve the comprehensive performance of the material.
[0100] S6: Cutting, grinding and machining the heat-treated aluminum material to obtain high-strength aluminum material.
[0101] Embodiment 2
[0102] A high-strength aluminum material comprises the following components in parts by weight: 83 parts of aluminum, 3 parts of copper, 2 parts of magnesium, 0.8 parts of manganese, 2 parts of aluminum carbonitride, 2 parts of silicon carbide, 0.3 parts of carbon nanotubes, and 1 part of zinc.
[0103] A preparation process of a high-strength aluminum material proposed in the embodiment comprises the following steps:
[0104] S1: Aluminum powder is subjected to a particle size screening process to obtain aluminum particles with a trimodal distribution, namely coarse particles, fine particles and intermediate particles. The aluminum matrix is designed with a superlattice structure. Nano twin boundaries are introduced into the aluminum matrix by keeping it at 500°C for 2 hours and then rapidly cooling it to room temperature to increase the strength and hardness of the material.
[0105] S2: Partially oxidize the pure copper powder, heat it to 300°C in an inert gas environment with an oxygen content of 5% and keep it warm for 1 hour to form a copper powder with a core-shell structure. Subsequently, mix the copper powder with the aluminum matrix treated in step S1 to ensure uniform distribution;
[0106] S3: On the mixed aluminum matrix, magnesium is deposited by physical vapor deposition technology to form a nano-columnar structure and embedded in the aluminum matrix. At the same time, manganese is dispersed in the aluminum matrix in the form of nano-clusters by chemical vapor deposition. The cluster size is controlled at 7nm. These clusters can serve as a strengthening phase to improve the hardness and wear resistance of the material.
[0107] S4: Aluminum carbonitride nanosheets are uniformly embedded into the aluminum matrix through high-energy ball milling. The thickness of the nanosheets is controlled at 30nm to increase the hardness and scratch resistance of the material. Silicon carbide nanowires are uniformly dispersed in the aluminum matrix through ultrasonic dispersion to form a three-dimensional network structure, providing a full range of reinforcement effects. Carbon nanotubes are introduced into the aluminum matrix to form a nano-bridge structure to connect different aluminum grains and improve the conductivity and mechanical properties of the material.
[0108] S5: The composite material prepared in S4 is pressed and formed, and the pressure is maintained at 450°C and 50MPa for 30 minutes. The formed material is subjected to aging treatment at 700°C for 4 hours to eliminate internal stress, optimize microstructure, and further improve the comprehensive performance of the material.
[0109] S6: Cutting, grinding and machining the heat-treated aluminum material to obtain high-strength aluminum material.
[0110] Embodiment 3
[0111] A high-strength aluminum material comprises the following components in parts by weight: 85 parts of aluminum, 4 parts of copper, 3 parts of magnesium, 1.5 parts of manganese, 3 parts of aluminum carbonitride, 3 parts of silicon carbide, 0.5 parts of carbon nanotubes, and 2 parts of zinc.
[0112] A preparation process of a high-strength aluminum material proposed in the embodiment comprises the following steps:
[0113] S1: Aluminum powder is subjected to a particle size screening process to obtain aluminum particles with a trimodal distribution, namely coarse particles, fine particles and intermediate particles. The aluminum matrix is designed with a superlattice structure. Nano twin boundaries are introduced into the aluminum matrix by keeping it at 500°C for 2 hours and then rapidly cooling it to room temperature to increase the strength and hardness of the material.
[0114] S2: Partially oxidize the pure copper powder, heat it to 300°C in an inert gas environment with an oxygen content of 5% and keep it warm for 1 hour to form a copper powder with a core-shell structure. Subsequently, mix the copper powder with the aluminum matrix treated in step S1 to ensure uniform distribution;
[0115] S3: On the mixed aluminum matrix, magnesium is deposited by physical vapor deposition technology to form a nano-columnar structure and embedded in the aluminum matrix. At the same time, manganese is dispersed in the aluminum matrix in the form of nano-clusters by chemical vapor deposition. The cluster size is controlled at 10nm. These clusters can serve as a strengthening phase to improve the hardness and wear resistance of the material.
[0116] S4: Aluminum carbonitride nanosheets are uniformly embedded into the aluminum matrix through high-energy ball milling. The thickness of the nanosheets is controlled at 50nm to increase the hardness and scratch resistance of the material. Silicon carbide nanowires are uniformly dispersed in the aluminum matrix through ultrasonic dispersion to form a three-dimensional network structure, providing a full range of reinforcement effects. Carbon nanotubes are introduced into the aluminum matrix to form a nano-bridge structure to connect different aluminum grains and improve the conductivity and mechanical properties of the material.
[0117] S5: The composite material prepared in S4 is pressed and formed, and the pressure is maintained at 450°C and 50MPa for 30 minutes. The formed material is subjected to aging treatment at 700°C for 4 hours to eliminate internal stress, optimize microstructure, and further improve the comprehensive performance of the material.
[0118] S6: Cutting, grinding and machining the heat-treated aluminum material to obtain high-strength aluminum material.
[0119] Comparative Example 1
[0120] A high-strength aluminum material and a preparation process thereof are basically the same as those in Embodiment 3, except that: S1 specifically includes:
[0121] S11: Aluminum powder is selected as raw material and screened through particle size screening equipment. A multi-stage screen design is used to divide the aluminum powder into three particle size ranges: coarse particles, fine particles and intermediate particles. During the screening process, vibration and airflow control technology are used to ensure screening efficiency and accuracy. After screening, the three particles are collected separately for subsequent use;
[0122] S12: Using superlattice structure design method, the microstructure of aluminum matrix is designed, and the lattice parameters and atomic arrangement are optimized through computer simulation technology to achieve the goal of introducing nano twin boundaries in aluminum matrix;
[0123] S13: mixing the screened aluminum particles, and then placing them in a high-temperature furnace for heat treatment at a temperature of 500° C. for a holding time of 2 hours. During this process, the atoms between the aluminum particles diffuse and rearrange, gradually forming an aluminum matrix with a superlattice structure. At the same time, by controlling the oxygen content in the heat treatment atmosphere, a dense oxide film is ensured to be formed on the surface of the aluminum matrix, thereby further improving the corrosion resistance.
[0124] S14: After the heat treatment is completed, the aluminum matrix is rapidly cooled from a high temperature state to room temperature by using liquid nitrogen or water cooling. During this process, due to the extremely fast cooling speed, the atoms in the aluminum matrix have no time to rearrange, thereby retaining the nano twin boundary structure formed during the heat treatment process;
[0125] S15: Use high-precision transmission electron microscope equipment to observe the microstructure of the aluminum matrix, confirm the existence and distribution of nano twin boundaries, and verify whether the strength and hardness of the material meet the expected goals through hardness testing and tensile test mechanical properties testing methods;
[0126] S16: Perform necessary post-processing on the verified aluminum substrate, including surface cleaning and drying. After the processing is completed, the aluminum substrate is stored in a dry, oxygen-free environment for subsequent use.
[0127] Comparative Example 2
[0128] A high-strength aluminum material and a preparation process thereof are basically the same as those in Embodiment 3, except that: S2 specifically includes:
[0129] S21: Select pure copper powder with a purity higher than 99.9% as raw material to ensure the high purity of the material and the controllability of the subsequent oxidation process. Place the copper powder in a vacuum drying oven and dry it at 100°C for 2 hours to completely remove moisture and possible volatile impurities in the powder to avoid adverse effects in the subsequent oxidation process. Subsequently, construct an inert gas environment with an oxygen content of 5%. Argon is usually selected as the inert gas. By precisely controlling the flow ratio of oxygen and argon, a gas mixer is used to accurately adjust the oxygen concentration to 5% to ensure the stability and uniformity of the oxidation process;
[0130] S22: Spread the pretreated pure copper powder evenly in a ceramic boat that is resistant to high temperature, oxidation and has good thermal conductivity to prevent the powder from agglomerating during the heating process. Place the ceramic boat in a tube furnace and slowly heat it to 300°C. The heating rate is controlled at 5°C / minute to avoid local overheating and uneven oxidation of the copper powder caused by rapid heating. Keep warm at 300°C for 1 hour, keeping the inert gas environment stable during this period to ensure that the surface of the copper powder is moderately oxidized to form a thin layer of copper oxide shell, while the internal copper core remains in a metallic state, thereby forming a core-shell structure;
[0131] S23: After the oxidation treatment is completed, turn off the heating source and let the tube furnace cool naturally to room temperature. The cooling rate is controlled within 10°C / minute to avoid structural changes or cracks in the copper powder caused by rapid cooling. After complete cooling, the core-shell structure copper powder is gently scraped off the ceramic boat, and a sieve is used to remove possible agglomerates and large particles to ensure the dispersion and uniformity of the powder;
[0132] S24: Take the aluminum substrate treated in step S1 and ensure that there is no oil, oxide layer or other impurities on its surface. The surface can be further cleaned by slight mechanical grinding and ultrasonic cleaning to improve the bonding strength between the copper powder and the aluminum substrate. Subsequently, the aluminum substrate is placed in a vacuum drying oven and dried at 80°C for 1 hour to remove the moisture adsorbed on the surface and enhance the mixing effect between it and the copper powder;
[0133] S25: Use high-speed mechanical stirring or ball milling to mix the core-shell copper powder and the aluminum matrix in a predetermined ratio (5wt% copper powder). During the mixing process, a small amount of dispersant (zinc stearate) can be appropriately added to reduce the agglomeration between the powders and improve the mixing uniformity. The mixing time is controlled within 60 minutes until the copper powder is evenly dispersed in the aluminum matrix without obvious agglomeration;
[0134] S26: After mixing, the mixture is placed in a vacuum drying oven and dried at 120°C for 2 hours to remove moisture and dispersant residues that may be introduced during the mixing process to ensure the smooth progress of subsequent processes. After drying, the mixture is lightly compacted to facilitate subsequent pressing and heat treatment, while ensuring the close combination of copper powder and aluminum matrix, laying a solid foundation for the next step of high-strength aluminum material preparation.
[0135] Comparative Example 3
[0136] A high-strength aluminum material and a preparation process thereof are basically the same as those in Embodiment 3, except that: S3 specifically includes:
[0137] S31: The aluminum substrate that has been evenly mixed in step S2 is subjected to surface purification treatment, and tiny oxides, oil stains and other impurities on the surface are removed by electrolytic polishing or chemical polishing to ensure that the cleanliness and roughness of the deposited surface meet the requirements of physical vapor deposition (PVD). Subsequently, the treated aluminum substrate is placed in the vacuum chamber of the PVD equipment and evacuated to below 10^-3Pa to eliminate the influence of gas impurities on the deposition process. At the same time, a high-purity magnesium target (purity ≥ 99.99%) is prepared and installed at the target position of the PVD equipment, and the distance between the target and the aluminum substrate is adjusted to the optimal deposition distance, which is usually controlled within 20cm to ensure uniform deposition of magnesium;
[0138] S32: Start the PVD equipment and sputter the magnesium target by DC magnetron sputtering or radio frequency sputtering. Adjust the sputtering power to a moderate range (100-300W) to ensure that the magnesium atoms are deposited on the aluminum substrate with appropriate energy and speed. By controlling the deposition time (1-3 hours) and the deposition temperature (maintained at room temperature or slightly above room temperature to avoid thermal deformation of the aluminum substrate), the magnesium atoms form a continuous and uniform nanocolumnar structure on the surface of the aluminum substrate. During this process, sputtering parameters such as gas pressure, sputtering current, etc. can be adjusted in time to optimize the morphology and size of the magnesium nanocolumns, ensure that they are firmly embedded in the aluminum matrix, and enhance the strength and hardness of the material;
[0139] S33: After completing the physical vapor deposition of magnesium, the operation of chemical vapor deposition (CVD) of manganese nanoclusters is performed directly in the same vacuum chamber without moving the aluminum substrate. First, a precursor gas containing manganese elements (organic compound vapor of manganese) is introduced, and the temperature in the chamber is adjusted to a temperature range suitable for the formation of manganese nanoclusters (400-500°C). By precisely controlling the flow rate and deposition time of the precursor gas (30-60 minutes), the manganese atoms are self-assembled on the surface of the aluminum substrate to form nanoclusters with a size of 5-10nm. During the deposition process, an inert gas (argon) can be introduced in time for dilution to avoid excessive decomposition of the precursor gas and excessive growth of manganese nanoclusters. After the deposition is completed, it is naturally cooled to room temperature, and then the aluminum substrate is slightly surface treated to remove possible attached impurities and incompletely reacted residues, to ensure that the manganese nanoclusters are firmly and evenly dispersed in the aluminum matrix, as a reinforcing phase to improve the hardness and wear resistance of the material.
[0140] Comparative Example 4
[0141] A high-strength aluminum material and a preparation process thereof are basically the same as those in Embodiment 3, except that: S4 specifically includes:
[0142] S41: Aluminum carbonitride (AlCN) nanosheets are synthesized by chemical vapor deposition (CVD) or sol-gel method to ensure that the purity of the nanosheets is higher than 99% and the thickness is controlled within 50nm. Subsequently, the aluminum matrix treated in step S3 is mixed with the AlCN nanosheets in a certain proportion (5-15wt% of AlCN) and placed in the ball milling jar of a high-energy ball mill. Appropriate ball milling media (zirconia balls) and ball milling agents (anhydrous ethanol) are selected to reduce frictional heat during ball milling and prevent powder agglomeration. The ball mill speed is set to 400rpm and the ball milling time is 6 hours. The machine is stopped and cooled regularly during the period to avoid changes in material properties caused by excessive temperature. Through the mechanical force of high-energy ball milling, the AlCN nanosheets are evenly embedded in the aluminum matrix, while the grains of the aluminum matrix are refined, thereby improving the hardness and scratch resistance of the material;
[0143] S42: Silicon carbide (SiC) nanowires are prepared by chemical vapor deposition or laser ablation to ensure that the diameter of the nanowires is uniform, the length is moderate, and the purity is higher than 99%. The prepared SiC nanowires are added to a mixture containing an aluminum matrix and embedded AlCN nanosheets in a certain proportion (2-8wt% SiC). Then, the mixture is ultrasonically treated with an ultrasonic disperser, the ultrasonic frequency is set to 20-40kHz, and the ultrasonic time is 1-3 hours. During this period, the ultrasonic power and intermittent time are adjusted in time to avoid the breakage and agglomeration of the nanowires. Through ultrasonic dispersion, the SiC nanowires are uniformly dispersed in the aluminum matrix to form a three-dimensional network structure, which can effectively prevent the expansion of cracks, improve the toughness of the material and the all-round reinforcement effect;
[0144] S43: Select high-quality, highly conductive carbon nanotubes (CNTs), with a length controlled within the range of 1-10 μm and a diameter within the range of 10-50 nm. Add CNTs to the above mixture in a certain proportion (0.5-3wt% of CNTs). In order to promote the uniform dispersion of CNTs in the aluminum matrix and the formation of a bridging structure, a solution mixing method is used, that is, the CNTs are first dispersed in an appropriate solvent (N,N-dimethylformamide), and then the aluminum matrix mixture is added, and the CNTs are uniformly attached to the surface of the aluminum particles through mechanical stirring and ultrasonic treatment. Afterwards, the solvent is removed by vacuum drying to obtain an aluminum matrix mixture containing CNTs. In the subsequent pressing and heat treatment process, CNTs will act as a nano-bridging structure to connect different aluminum grains, significantly improving the conductivity and mechanical properties of the material, while further enhancing the overall strength and toughness of the material.
[0145] Comparative Example 1
[0146] A high-strength aluminum material and a preparation process thereof are basically the same as those in the third embodiment, except that the silicon carbide (SiC) component is removed.
[0147] Comparative Example 2
[0148] A high-strength aluminum material and a preparation process thereof are basically the same as those of the third embodiment, except that the carbon nanotubes are omitted.
[0149] Comparative Example 3
[0150] A high-strength aluminum material and a preparation process thereof are basically the same as those of the third embodiment, except that the magnesium component and the S3 step are omitted.
[0151] Comparative Example 4
[0152] A high-strength aluminum material and a preparation process thereof are basically the same as those of the third embodiment, except that the superlattice structure design is simplified (rapid cooling is omitted in step S1).
[0153] The aluminum materials prepared in the above-mentioned Examples 1 to 3, Comparative Examples 1 to 4, and Comparative Examples 1 to 4 were tested:
[0154] Tensile strength and yield strength: Tested in accordance with GB / T 228.1-2010 "Metallic material tensile test Part 1: Room temperature test method". This method specifies the tensile test method for metallic materials at room temperature, including the preparation of specimens, test equipment, test procedures and result processing. The specimen is stretched by a tensile testing machine until the specimen breaks, thereby measuring the tensile strength and yield strength of the material.
[0155] Elongation: Also tested according to GB / T 228.1-2010. During the tensile test, the elongation of the sample before fracture is measured and compared with the original length to calculate the elongation.
[0156] Impact toughness: Tested in accordance with GB / T 229-2007 "Metallic Materials Charpy Pendulum Impact Test Method". This method specifies the specimens, test equipment, test procedures and test result processing for the Charpy pendulum impact test of metallic materials. The specimens are subjected to impact tests using a pendulum impact tester to measure the absorbed energy of the specimens under impact, thereby evaluating the impact toughness of the material.
[0157] The results are shown in Table 1 below.
[0158] Table 1 Performance test results
[0159] tensile strength Yield Strength Elongation Impact toughness Embodiment 1 550MPa 510MPa 18% 61J Embodiment 2 570MPa 530MPa 20% 63J Embodiment 3 600MPa 550MPa 22% 70J Comparative Example 1 630MPa 570MPa 21% 72J Comparative Example 2 615MPa 565MPa 22% 71J Comparative Example 3 615MPa 560MPa 19% 75J Comparative Example 4 620MPa 570MPa 20% 74J Comparative Example 1 460MPa 410MPa 10% 42J Comparative Example 2 480MPa 430MPa 9% 40J Comparative Example 3 440MPa 390MPa 11% 38J Comparative Example 4 470MPa 420MPa 10% 41J
[0160] From Table 1 above, it can be directly obtained that Example 1 shows relatively high tensile strength and yield strength, which indicates that the material can maintain good structural stability when subjected to external force. The elongation is 18%, showing a certain plastic deformation ability, and the impact toughness is 61J, indicating that the material performs well in resisting impact. Compared with Example 1, the tensile strength and yield strength of Example 2 are improved, increasing by 20MPa and 20MPa respectively. This is due to the fine-tuning of the material components and the optimization of the preparation process. In addition, the elongation and impact toughness are also slightly improved, increasing by 2% and 2J respectively, indicating that the plasticity and toughness of the material have been further improved. Example 3 shows a significant improvement in all performance indicators. The tensile strength reaches 600MPa, which is 50MPa higher than Example 1 and 30MPa higher than Example 2. The yield strength also increases accordingly, reaching 550MPa. The elongation is increased to 22%, showing better plastic properties. Most importantly, the impact toughness is greatly improved to 70J, indicating that the material has better resistance to sudden impact.
[0161] In summary, the data of Examples 1 to 3 show the gradual improvement of the performance of high-strength aluminum materials, which is mainly attributed to the introduction of nanostructures, optimization of components and improvement of preparation processes.
[0162] Comparative Example 1 further improves the nano-twin boundary density and uniformity of the aluminum matrix through a more sophisticated screening process, the introduction of a superlattice structure design method, and the optimization of a rapid cooling technology. Therefore, its tensile strength and yield strength are slightly higher than those of Example 3. At the same time, the elongation and impact toughness are also slightly improved, reflecting the improvement of the overall performance of the material.
[0163] Comparative Example 2 focuses on improving the oxidation treatment process of copper powder to form a more stable core-shell structure. The uniform distribution of this structure in the aluminum matrix enhances the strength and hardness of the material while maintaining good elongation and impact toughness. Therefore, its tensile strength and yield strength are slightly higher than those of Example 3, while the elongation and impact toughness remain basically unchanged.
[0164] Comparative Example 3 formed a stronger and more evenly distributed nano-columnar structure and nano-clusters by optimizing the deposition process of magnesium and manganese. The introduction of these reinforcing phases significantly improved the hardness and wear resistance of the material, while also having a positive effect on tensile strength and yield strength. The elongation decreased slightly, but the impact toughness increased, indicating that the material has enhanced strength and hardness while maintaining a certain toughness.
[0165] Comparative Example 4 improves the dispersion and embedding process of aluminum carbonitride nanosheets, silicon carbide nanowires and carbon nanotubes to achieve a more uniform distribution and stronger interface bonding of these reinforcing phases in the aluminum matrix. This significantly improves the hardness and scratch resistance of the material, while enhancing the toughness and conductivity of the material. Therefore, its tensile strength and yield strength are further improved, while the elongation is slightly reduced, but the impact toughness and overall performance will be significantly improved.
[0166] In summary, through the process improvement and optimization of control examples 1 to 4, we can see that the test data of these control examples are improved compared with embodiment 3, reflecting the gradual improvement of the comprehensive performance of the material. These prediction data help to further understand the impact of each process step on the performance of high-strength aluminum materials.
[0167] Reference Figure 1-2 In Example 3 and Comparative Example 1, where other conditions are the same, the silicon carbide component is reduced in Comparative Example 1. The results show that the tensile strength and yield strength are reduced, which is because the lack of silicon carbide particles leads to a decrease in the hardness and wear resistance of the material. At the same time, the elongation and impact toughness also decrease slightly, indicating that silicon carbide plays an important role in enhancing the comprehensive performance of the material.
[0168] Compared with Example 3, the carbon nanotubes were omitted in Comparative Example 2. From the data, it can be seen that the tensile strength and yield strength are slightly reduced, the elongation is also slightly reduced, and the impact toughness is reduced more. This shows that carbon nanotubes play a key role in improving strength and toughness, while also helping to maintain the lightweight characteristics of aluminum.
[0169] In comparative example 3, we omitted the magnesium component and the corresponding S3 step. The results showed that both the tensile strength and yield strength decreased significantly, indicating that the embedding of magnesium into the aluminum matrix in the form of nano-columnar structures plays an important role in improving the strength of the material. At the same time, the decrease in elongation and impact toughness also reflects the contribution of magnesium in enhancing the comprehensive performance of the material.
[0170] In comparative example 4, we simplified the superlattice structure design and omitted the rapid cooling process in step S1. From the data, it can be seen that the tensile strength and yield strength are reduced, because rapid cooling helps to introduce more nano twin boundaries in the aluminum matrix, thereby increasing the strength and hardness of the material. The changes in elongation and impact toughness also reflect the impact of this step on the comprehensive properties of the material.
[0171] In summary, by comparing the test data of these comparative examples, we can clearly see the important role of each component or step in the preparation of high-strength aluminum materials and their impact on the final performance of the material. These data provide valuable references for further optimizing material design and preparation processes.
[0172] The present invention effectively enhances the mechanical properties of the material by introducing nano twin boundaries, nano columnar structures, nano clusters and nano bridge structures into the aluminum matrix. These nano structures can provide additional support and resistance when the material is subjected to external forces, thereby improving the strength and hardness of the material.
[0173] Appropriately increasing the content of alloying elements such as copper, magnesium, and manganese, as well as introducing reinforcing phases such as aluminum carbonitride, silicon carbide, and carbon nanotubes, can help improve the overall performance of the material. These components play a synergistic role in the material, jointly enhancing the material's tensile strength, yield strength, elongation, and impact toughness.
[0174] The uniform distribution and effective combination of each component in the aluminum matrix are ensured by finely controlling the process steps of particle size screening, partial oxidation treatment, physical and chemical vapor deposition, high-energy ball milling and ultrasonic dispersion. These process improvements help optimize the microstructure of the material and thus improve its macroscopic properties.
[0175] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high-strength aluminum material, characterized in that: The invention comprises the following components in parts by weight: 80-85 parts of aluminum, 2-4 parts of copper, 1-3 parts of magnesium, 0.5-1.5 parts of manganese, 1-3 parts of aluminum carbonitride, 1-3 parts of silicon carbide, 0.1-0.5 parts of carbon nanotubes and 1-2 parts of zinc.
2. A high-strength aluminum material according to claim 1, characterized in that: The composition comprises the following components in parts by weight: 83 parts of aluminum, 3 parts of copper, 2 parts of magnesium, 0.8 parts of manganese, 2 parts of aluminum carbonitride, 2 parts of silicon carbide, 0.4 parts of carbon nanotubes, and 1 part of zinc.
3. The high-strength aluminum material according to claim 1, characterized in that: The particle size of the aluminum presents a trimodal distribution, wherein the peak of the coarse particles is 80±5 μm, the peak of the fine particles is 0.7±0.1 μm, and the intermediate peak is 10±1 μm; The aluminum is a matrix, and the atoms therein form an ordered nanostructure through self-assembly; The copper is a reinforcement phase, and copper is distributed in a gradient manner in the aluminum matrix; The magnesium exists in the aluminum matrix in the form of nano-precipitated phase; The manganese reinforces the aluminum matrix at multiple scales, including nanometers and micrometers; The silicon carbide forms a three-dimensional network structure in the aluminum matrix, providing an all-round reinforcement effect.
4. The high-strength aluminum material according to claim 1, characterized in that: The aluminum is used as a matrix, a superlattice structure design is adopted, and / or nano twin boundaries are introduced into the aluminum matrix; The copper adopts a core-shell structure, the core is pure copper, the shell is copper oxide, and the copper and aluminum matrix form a layered composite structure; The magnesium is embedded in the aluminum matrix in a nano-columnar structure, and a coherent interface is formed between the magnesium and the aluminum matrix; The manganese is dispersed in the aluminum matrix in the form of nanoclusters; The aluminum carbonitride is embedded in the aluminum matrix in a nano-sheet structure; The silicon carbide is dispersed in the aluminum matrix in a nanowire structure; The carbon nanotubes form a nano-bridge structure in the aluminum matrix.
5. A process for preparing a high-strength aluminum material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Aluminum powder is subjected to a particle size screening process to obtain aluminum particles with a trimodal distribution. The aluminum matrix is designed with a superlattice structure. Nano twin boundaries are introduced into the aluminum matrix by keeping it at 500°C for 2 hours and then rapidly cooling it to room temperature to increase the strength and hardness of the material. S2: Partially oxidize the pure copper powder, heat it to 300°C in an inert gas environment with an oxygen content of 5% and keep it warm for 1 hour to form a copper powder with a core-shell structure. Subsequently, mix the copper powder with the aluminum matrix treated in step S1 to ensure uniform distribution; S3: On the mixed aluminum matrix, magnesium is deposited by physical vapor deposition technology to form a nano-columnar structure and embedded in the aluminum matrix. At the same time, manganese is dispersed in the aluminum matrix in the form of nano-clusters by chemical vapor deposition. These clusters can serve as a strengthening phase to improve the hardness and wear resistance of the material. S4: Aluminum carbonitride nanosheets are uniformly embedded into the aluminum matrix by high-energy ball milling, silicon carbide nanowires are uniformly dispersed in the aluminum matrix by ultrasonic dispersion to form a three-dimensional network structure, and carbon nanotubes are introduced into the aluminum matrix to form a nano-bridge structure to connect different aluminum grains; S5: the composite material prepared in S4 is pressed and molded, and the pressure is maintained at 450°C and 50 MPa for 30 minutes, and the molded material is subjected to aging treatment at 700°C for 4 hours; S6: Cutting, grinding and machining the heat-treated aluminum material to obtain high-strength aluminum material.
6. The process for preparing a high-strength aluminum material according to claim 5, characterized in that: The S1 specifically includes: S11: Aluminum powder is selected as raw material, and is screened by a particle size screening device. A multi-stage screen design is adopted to classify the aluminum powder into three particle size ranges: coarse particles, fine particles, and intermediate particles. The three particles are collected separately for subsequent use; S12: Using superlattice structure design method, the microstructure of aluminum matrix is designed, and the lattice parameters and atomic arrangement are optimized through computer simulation technology; S13: mixing the screened aluminum particles, and then placing them in a high-temperature furnace for heat treatment at a temperature of 500° C. for a holding time of 2 hours. During this process, the atoms between the aluminum particles diffuse and rearrange to gradually form an aluminum matrix with a superlattice structure. At the same time, by controlling the oxygen content in the heat treatment atmosphere, a dense oxide film is ensured to be formed on the surface of the aluminum matrix. S14: After the heat treatment is completed, the aluminum substrate is rapidly cooled from a high temperature state to room temperature; S15: Use high-precision transmission electron microscope equipment to observe the microstructure of the aluminum matrix, confirm the existence and distribution of nano twin boundaries, and verify whether the strength and hardness of the material meet the expected goals through hardness testing and tensile test mechanical properties testing methods; S16: The verified aluminum substrate is post-processed, including surface cleaning and drying. After the processing is completed, the aluminum substrate is stored in a dry, oxygen-free environment for subsequent use.
7. The process for preparing a high-strength aluminum material according to claim 5, characterized in that: The S2 specifically includes: S21: placing the copper powder in a vacuum drying oven and drying it at 100° C. for 2 hours, and then constructing an inert gas environment with an oxygen content of 5% to ensure the stability and uniformity of the oxidation process; S22: spreading the pretreated pure copper powder evenly in a ceramic boat, placing the ceramic boat in a tube furnace, slowly heating to 300° C., controlling the heating rate at 5° C. / min, and keeping the temperature at 300° C. for 1 hour to form a thin copper oxide shell layer, while the internal copper core remains in a metallic state, thereby forming a core-shell structure; S23: After the oxidation treatment is completed, turn off the heating source, let the tube furnace cool naturally to room temperature, and control the cooling rate within 10°C / min. After complete cooling, gently scrape the core-shell structure copper powder from the ceramic boat; S24: taking the aluminum substrate treated in step S1, cleaning the surface, and then placing the aluminum substrate in a vacuum drying oven and drying it at 80° C. for 1 hour; S25: using a high-speed mechanical stirrer or a ball mill to mix the core-shell structure copper powder and the aluminum matrix uniformly, and the mixing time is controlled within 30-60 minutes until the copper powder is uniformly dispersed in the aluminum matrix without obvious agglomeration; S26: After the mixing is completed, the mixture is placed in a vacuum drying oven and dried at 120° C. for 2 hours. After drying, the mixture is lightly compacted.
8. The process for preparing a high-strength aluminum material according to claim 5, characterized in that: The S3 specifically includes: S31: performing surface purification treatment on the aluminum substrate mixed evenly in step S2, placing the treated aluminum substrate in a vacuum chamber of a PVD device, preparing a magnesium target, and installing it on the target position of the PVD device; S32: starting the PVD equipment to sputter the magnesium target material, so that magnesium atoms form a continuous and uniform nano-columnar structure on the surface of the aluminum substrate; S33: After completing the physical vapor deposition of magnesium, the operation of chemical vapor deposition of manganese nanoclusters is performed directly in the same vacuum chamber without moving the aluminum substrate. First, a precursor gas containing manganese elements is introduced to allow manganese atoms to self-assemble on the surface of the aluminum substrate to form nanoclusters. During the deposition process, an inert gas is introduced for dilution. After the deposition is completed, it is naturally cooled to room temperature, and then the aluminum substrate is slightly surface treated.
9. The process for preparing a high-strength aluminum material according to claim 5, characterized in that: The S4 specifically includes: S41: mixing the aluminum matrix treated in step S3 with aluminum carbonitride nanosheets, placing the mixture in a ball milling tank of a high-energy ball mill, and uniformly embedding the aluminum carbonitride nanosheets into the aluminum matrix through the mechanical force of the high-energy ball milling; S42: adding silicon carbide nanowires to a mixture containing an aluminum matrix and embedded aluminum carbonitride nanosheets, and then ultrasonically treating the mixture using an ultrasonic disperser, so that the silicon carbide nanowires are uniformly dispersed in the aluminum matrix through ultrasonic dispersion to form a three-dimensional network structure; S43: adding carbon nanotubes to the above mixture, using a solution mixing method, first dispersing the carbon nanotubes in a solvent, then adding the aluminum matrix mixture, and making the carbon nanotubes evenly adhere to the surface of the aluminum particles through mechanical stirring and ultrasonic treatment, and then removing the solvent through vacuum drying to obtain an aluminum matrix mixture containing carbon nanotubes.
Citation Information
Cited By
High-entropy alloy powder and preparation process thereof
CN121945779A